Spatial Epidemiology of the Stony-Coral-Tissue-Loss Disease in Florida - Muller, Erinn M.; Sartor, Constance; Alcaraz, Nicholas I.; van Woesik, Robert (Frontiers in Marine Science, 2020)
The stony-coral-tissue-loss disease has recently caused widespread loss of coral along the Florida reef tract. Yet little is known about where, when, and why this coral disease outbreak occurred. In the absence of a definitive pathogen, it is essential to characterize the ecology of the disease and document the spatio-temporal dynamics of the outbreak. Here, we investigate the epizootiology of the stony-coral-tissue-loss disease at multiple spatial and temporal scales along the Florida reef tract from May 2014 to December 2017. We used spatial interpolation to characterize the disease hotspots, Ripley’s K analysis to examine contagion, a spatio-temporal model to assess rates of spread, and a Bayesian model to examine ecological and environmental covariates that may have influenced the occurrence and severity of the outbreak. Our results show that the disease affected reefs at the scale of hundreds of kilometers, with significant clusters of up to 140 km. The epizootic clearly followed a contagion model, suggesting that the disease was highly contagious. The rate of spread of the epizootic was linear and moved slightly faster to the north (~ 100 m d-1) than to the south (~ 92 m d-1). The difference in rate of spread between the north and south direction may indicate currents facilitated transmission. The analyzed dataset showed that the epizootic affected at least 19 coral species and that deep and diverse sites were at greater risk of the disease than shallow and low diversity sites.